Faktor-Faktor yang Mempengaruhi Tingkat Pendidikan Anak Nelayan di Kenagarian Muara Kandis Punggasan Kecamatan Linggo Sari Baganti - Yulanda, Tesa - (Pendidikan Geografi, 2014)
This study aims to look at the effect of parental income on childrens education level of fishermen, to see the effect of learning motivation of children to child education level of fishermen, seeing the influence of the interaction in the family on, level of education, and look at the effect of parental income level, childrens learning motivation , and interactions within the family together on the level of education of children of fishermen in the estuary Kenagarian Kandis Punggasan Linggo Sari subdistrict Baganti. This type of research is descriptive correlational. The study population was a whole head of fishing families totaling 375 households. The sample of respondents was determined by using proportional random sampling so that the sample taken 20% of respondents bejumlah 75 families, The conclusion of this study were (1) There is a significant effect of parental income on childrens education level Kenagarian estuary fishing in the District Punggasan Kandis Linggo Sari Baganti 0,452, (2) there is a significant influence childrens motivation to learn about the education level of fishermen fishing in children Kenagarian Muara District of Linggo Sari Kandis Punggasan Baganti of 0.419, (3) there is a significant interaction effect in the childs family to the education level of fishermen in the estuary Kenagarian Kandis Punggasan Linggo Sari subdistrict Baganti of 0.437, (4) there is a significant effect of parental income level , childrens motivation to learn fishing, and interactions within the family of the level of education of children of fishermen in Muara Kenagarian Kandis Punggasan Linggo Sari subdistrict Baganti at 0.574%.